Mengungkap Kesadaran Islami atas Riba pada Proses Pembelajaran Akuntansi - Rahmanti, Virginia Nur (Journal of Accounting and Investment, 2017)
This research aimed to know awareness of teachers (lecturers) specifically on subject of Financial Accounting including recognition, measurement, and reporting of â€œinterestâ€. Muslims believe that interest is forbidden as riba. Indeed, the practice of interest is not limited as Islamic issue, but it is viewed as universal issue based on housing bubble price cycle that may affect all sectors. By employing post-phenomenology as well as thought of Don Ihde, this research involving five diversified informant. The results showed that the subjects of Financial Accounting lecturer (Muslim) still stuck on "technology" (term of Ihde) in the form of international curriculum standards, reference books, and subject (course) planning.